New compounds Sr2LnBIIISnO7 (BIII – Sc, In) with two-layer perovskite-like structure - Titov, Yu.A.; Belyavina, N.M.; Markiv, V.Ya.; Slobodyanik, M. S.; Polubinskii, V.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The boundaries of regions with layered perovskite-like structure (LPS) in the rows of compounds Sr2LnBIIISnO7-type (BIII – Sc, In) are determined. The new scandatostannates Sr2LnScSnO7 (Ln – La, Pr) and indatostannates Sr2LaInSnO7 (Ln – La, Pr) have been synthesized by the solid-phase sintering from equimolar mixtures Sr3Sn2O7SrLn2Sc2O7 and Sr2SnO4 + LnInO3, and their crystal LPSs are determined by the Rietveld method. It is found that the LPS of Sr2LaScSnO7 belongs to the SrLn2Sc2O7-type structure (sp. gr. Fmmm), and the LPSs of Sr2PrScSnO7 and Sr2LnInSnO7 belong to the BaLa2In2O7-type structure (sp. gr. P42/mnm). The peculiarities of LPSs of Sr2LnBIIISnO7 (BIII – Sc, In) are analyzed.